Catalytic cracking method of PVC waste
By performing pyrolysis and cracking of PVC waste products in the presence of zeolite catalysts, the problems of low selectivity for useful components and high chlorine content in the prior art are solved, and the effect of high selectivity for recycling of useful components and reducing chlorine content is achieved. And produce high-performance activated carbon through activation.
Patent Information
- Application Number
- CN202380049518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-26
- Filing Date
- 2023-10-25
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, when recirculating the polyvinyl chloride resin, it is difficult to improve the selectivity of useful components, and the chlorine content of harmful components in the product is relatively high.
PVC waste is pyrolytic cracking in the presence of zeolite catalysts with an average crystal size of 5-30 nm to improve selectivity for C2 or C3 gas compounds or C5 to C9 gasoline and produce high specific surface area by activating solid residues and pore volume activated carbon.
Highly selective recovery of useful components is achieved, and the chlorine content in the liquid product is significantly reduced, and the specific surface area and pore volume of activated carbon is increased.
Smart Images

Figure BDA0005206143580000081 
Figure BDA0005206143580000101 
Figure BDA0005206143580000121
Abstract
Description
Technical Field
[0004] The present invention relates to a method for catalytic cracking of PVC waste, which can obtain gas components as useful resources with high selectivity through catalytic cracking of PVC waste and reduce the content of harmful component chlorine in the product. [Background Technology]
[0005] Polyvinyl chloride resin is one of the five major commonly used resins, and its global production totaled more than 40 million tons as of 2018. Most of the used polyvinyl chloride resin is disposed of by landfill and incineration. However, in the case of landfill, there is a problem that the chlorine component in the polyvinyl chloride resin is converted into highly toxic substances in the land, and in the case of incineration, there is a problem that harmful substances such as dioxins are generated during the incineration process. In addition, in the case of landfill and incineration, the used polyvinyl chloride resin cannot be reused. Therefore, recently, with the great interest in sustainability, there is great interest in methods of recycling polyvinyl chloride instead of landfill and incineration.
[0006] A representative recycling method of polyvinyl chloride resin is a mechanical recycling method. In the mechanical recycling method, waste products of polyvinyl chloride resin are crushed, cleaned, dried and cast to be used as raw materials for new plastic products. The mechanical recycling method has the advantages of simple process and suitability for processing a large amount of waste products, but its disadvantage is that it is difficult to obtain a recycled product with uniform properties due to continuous changes in properties during the recycling process. Specifically, since polyvinyl chloride resin has poor thermal stability and optical stability, it is molded by mixing additives such as stabilizers in the resin. However, these additive components are denatured during the mechanical recycling process, making it difficult to maintain constant properties of polyvinyl chloride resin during the mechanical recycling process.
[0007] In order to solve the disadvantages of the mechanical recycling method, a chemical recycling method is used. In the chemical recycling method, various low-molecular components can be recovered from polyvinyl chloride by breaking the polymer chain of polyvinyl chloride, wherein the low-molecular components can be used again as raw materials in various fields through a purification method. The chemical recycling method chemically treats the polyvinyl chloride resin, so it can be easily applied even when the waste product is not sorted or contaminated, and has the advantage of not being limited by various types of additives present in the resin.
[0008] A representative chemical recycling method of polyvinyl chloride resin is a pyrolysis method. By pyrolyzing polyvinyl chloride resin under high temperature and oxygen-free conditions, components such as hydrocarbons, hydrogen chloride and char can be obtained. However, in this pyrolysis method, the type or content of the components in the obtained hydrocarbons may vary depending on the catalyst used or the pyrolysis conditions. If the selectivity for C2 or C3 gaseous compounds or C5 to C9 gasoline as useful resources in the obtained hydrocarbons can be improved, there is an advantage that the economy of the chemical recycling method can be further improved. Therefore, when the chemical recycling method is applied to the recycling method of polyvinyl chloride resin, it is necessary to study a method for further improving the selectivity for the above-mentioned useful components. [Summary of the invention]
[0009] [Technical issues]
[0010] The present invention aims to solve the above-mentioned problems of the prior art and to provide a method for recycling PVC wastes which can improve the selectivity to useful components by cracking the PVC wastes in the presence of a zeolite catalyst having an average crystal size of 5-30 nm.
[0011] Furthermore, the present invention aims to provide a method for producing activated carbon having a high specific surface area and pore volume by activating the solid residue formed according to the PVC catalytic cracking process.
[0012] [Technical solution]
[0013] In order to solve the above problems, the present invention provides a method for catalytically cracking PVC waste products, and a method for producing activated carbon from the solid residue obtained by the cracking.
[0014] Specifically, (1) the present invention provides a method for catalytic cracking of PVC waste, the method comprising the step (S1) of pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture, wherein the zeolite catalyst has an average crystal size of 5 nm to 30 nm.
[0015] (2) The present invention provides a method for catalytic cracking of PVC waste as described in (1) above, wherein the zeolite catalyst supports at least one metal selected from the group consisting of Ni, Cu, Fe and Mn.
[0016] (3) The present invention provides a method for catalytic cracking of PVC waste as described in (1) or (2) above, wherein the zeolite catalyst has mesopores with a diameter of 5 nm to 30 nm.
[0017] (4) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (3) above, wherein the BET specific surface area of the zeolite catalyst is 300 m 2 / g to 400m 2 / g.
[0018] (5) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (4) above, wherein the pore volume of the zeolite catalyst is 0.25 cm 3 / g to 0.35cm 3 / g.
[0019] (6) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (5) above, wherein the pyrolysis is carried out at 400°C to 500°C.
[0020] (7) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (6) above, wherein the pyrolysis is performed for 1 hour to 6 hours.
[0021] (8) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (7) above, wherein the PVC content of the PVC waste is 20% by weight or more.
[0022] (9) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (8) above, wherein the proportion of olefin products in the hydrocarbon mixture obtained in step (S1) is 20 mol% or more.
[0023] (10) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (9) above, wherein the hydrocarbon mixture obtained in step (S1) comprises a gaseous product, a liquid product and a solid residue.
[0024] (11) The present invention provides a method for catalytic cracking of PVC waste as described in any one of (1) to (10) above, wherein the Cl content in the liquid product is 1 wt% or less.
[0025] (12) The present invention provides a method for producing activated carbon, the method comprising the following steps:
[0026] Pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture (S1); and activating a solid residue in the hydrocarbon mixture (S2), wherein the zeolite catalyst has an average crystal size of 5 nm to 30 nm.
[0027] (13) The present invention provides a method for producing activated carbon as described in (12) above, wherein H 2 O or KOH for activation.
[0028] (14) The present invention provides a method for producing activated carbon as described in (12) or (13) above, wherein the BET specific surface area of the activated carbon is 250 m 2 / g or above.
[0029] (15) The present invention provides a method for producing activated carbon as described in any one of (12) to (14) above, wherein the pore volume of the activated carbon is 0.50 cm 3 / g to 1cm 3 / g.
[0030] [Beneficial Effects]
[0031] When the catalytic cracking method of PVC waste according to the present invention is used, C2 or C3 gaseous compounds, or C5 to C9 gasoline as useful components can be recovered with high selectivity.
[0032] Furthermore, when activated carbon is produced from the solid residue in the hydrocarbon mixture obtained by the catalytic cracking process of PVC waste according to the present invention, activated carbon having a large specific surface area and pore volume can be obtained. [Specific implementation method]
[0033] Hereinafter, the present invention will be described in more detail.
[0034] The terms or words used in the specification and claims of this application should not be construed as limited to their ordinary or dictionary meanings, but should be construed as meanings and concepts consistent with the technical spirit of the present invention, based on the principle that the inventor can fully define the concepts of the terms to best describe his invention.
[0035] Catalytic cracking method for PVC waste
[0036] As a result of studies on a method for chemically recycling PVC waste, the inventors of the present invention have confirmed that when PVC waste is pyrolyzed using a zeolite catalyst having an average crystal size of 5 to 30 nm, selectivity to C2 or C3 gaseous compounds or C5 to C9 gasoline as useful components in a finally obtained hydrocarbon mixture can be increased, thereby completing the present invention.
[0037] Therefore, the present invention provides a method for catalytic cracking of PVC waste, the method comprising the step (S1) of pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture, wherein the zeolite catalyst has an average crystal size of 5 to 30 nm.
[0038] Hereinafter, the catalytic cracking method of PVC waste provided by the present invention will be described in more detail.
[0039] PVC waste
[0040] The catalytic cracking of the present invention is applied to PVC waste, and one object of the present invention is to recover useful components from the PVC waste and recycle them.
[0041] The PVC waste subjected to catalytic cracking in the present invention is not particularly limited as long as it contains PVC products, and may be, for example, PVC molded products such as waste tarpaulins or waste electric wires. Meanwhile, in the present invention, the PVC content of the PVC waste may be 20% by weight or more, more preferably 30-40% by weight. If PVC waste having a PVC content less than the above amount is subjected to catalytic cracking, the selectivity for useful components may not be high enough due to the presence of components other than PVC in the waste. On the other hand, when the PVC content in the PVC waste is too high, the chlorine (Cl) content increases accordingly, and the high chlorine content may reduce the activity of the catalyst, hindering the smooth progress of the cracking reaction.
[0042] Meanwhile, in the present invention, a step (S0) of pretreating the PVC waste before pyrolyzing the PVC waste may be further included. The pretreatment may be used to remove impurities present in the PVC waste and increase the surface area by mechanically crushing the PVC waste. Specifically, the pretreatment may be a water washing and crushing process.
[0043] When the above pretreatment is performed, the content of impurities in the waste before pyrolysis can be substantially reduced to minimize side reactions caused by the presence of impurities, and the surface area of the waste can be increased to maximize the efficiency of the pyrolysis process.
[0044] Zeolite Catalyst
[0045] In the present invention, the pyrolysis of waste PVC is carried out in the presence of a zeolite catalyst. Zeolite catalysts are widely used in cracking reactions in industry. In particular, in the present invention, a zeolite catalyst having an average crystal size of 5-30 nm, preferably 10-20 nm, is used. When a catalyst having an average crystal size smaller than the above range is used for pyrolysis reaction, the strength of the catalyst acid sites is weakened, which leads to the problem of reduced cracking reaction efficiency. When a catalyst having an average crystal size greater than the above range is used, the problem of reduced selectivity for olefin products as useful components arises. It is particularly preferred that the average crystal size is 10-20 nm. The crystal size can be measured by directly observing the catalyst crystals through a transmission electron microscope (TEM).
[0046] Meanwhile, zeolite catalyst can be loaded with one or more metals selected from Ni, Cu, Fe and Mn, particularly preferably Ni.Even if the zeolite catalyst of the metal component listed above is not loaded, sufficient cracking reaction is also carried out.However, when using the catalyst of the above-mentioned metal component loaded, the technical advantage of existence is that the chlorine content in the final product can be further reduced.Since the chlorine component can serve as the impurity in the hydrocarbon mixture and can also serve as harmful substances, it is more desirable to reduce the chlorine content with respect to the efficiency and economy of the subsequent method.Simultaneously, when the above-mentioned metal is loaded on the zeolite catalyst, the content of the metal in the catalyst can be 1-10 weight %, particularly preferably 3-7 weight %.When the content of the metal in the catalyst is too small, the effect of the loaded metal is not obvious, and when the content of the metal in the catalyst is greater than the above-mentioned scope, it is not easy to load the metal itself.
[0047] In the catalytic cracking method of PVC waste according to the present invention, the zeolite catalyst may have mesopores with a diameter of 5 to 30 nm, preferably 10 to 20 nm, due to its nanocrystalline nature. In addition, the zeolite catalyst may have a diameter of 300 to 400 nm. 2 / g, preferably 320 to 380m 2 / g BET specific surface area. In addition, the pore volume of the zeolite catalyst can be 0.25-0.35cm 3 / g, preferably 0.26-0.33cm 3 / g. When the specific surface area and pore characteristics of the zeolite meet the above conditions, effective thermal decomposition and cracking can be carried out by ensuring a sufficiently large specific surface area. At the same time, in the present invention, the pore size and volume can be measured using the ASAP2020 device of Micromeritics. More specifically, after pretreating the catalyst sample at 300°C and vacuum for 3 hours, the argon isotherm adsorption curve was measured at 186°C using the above-mentioned equipment, and the pore size and volume can be calculated by the isotherm adsorption curve. The BET specific surface area can be calculated by the BET method using the adsorption amount in the P / P0=0.05 to 0.2 region of the isotherm adsorption curve, and the pore volume can be calculated from the adsorption amount at P / P0=0.95.
[0048] Pyrolysis
[0049] According to the present invention, a hydrocarbon mixture, more particularly useful components, can be obtained by pyrolyzing the above-mentioned PVC waste products over the above-mentioned zeolite catalyst.
[0050] In the present invention, in order to perform pyrolysis, the PVC waste should be heated to a certain temperature or above. More specifically, the pyrolysis may be performed at 300 to 500° C., preferably 350 to 450° C. If the pyrolysis temperature is lower than the above range, the polymer chains of PVC may not be sufficiently broken, and if the pyrolysis temperature is significantly higher than the above range, there may be a problem that the formed useful components, particularly C5 to C9 gasoline, are additionally cracked.
[0051] In addition, the pyrolysis can be carried out for 1-6 hours, preferably 1-4 hours. If the pyrolysis time is too short, the PVC may not be fully pyrolyzed. If the pyrolysis time is too long, even if there is no actual pyrolysis reaction, too much energy will be consumed, which will reduce the economic feasibility of the pyrolysis process.
[0052] Meanwhile, the chlorine in the PVC chain may decompose into hydrogen chloride during the pyrolysis process. Therefore, in order to recover the hydrogen chloride produced during the pyrolysis process, the reactor performing the pyrolysis may be equipped with a separate gas collection device.
[0053] Hydrocarbon mixture
[0054] By the above-mentioned pyrolysis method, a hydrocarbon mixture containing useful components can be formed from PVC waste. The hydrocarbon mixture may include gaseous products, liquid products and solid residues. The gaseous mixture may include C2 or C3 gaseous compounds, and the liquid products may include C5 to C9 gasoline. More specifically, the liquid products may include oily components such as gasoline, kerosene, diesel and wax.
[0055] At the same time, the Cl content in the liquid product can be 1% by weight or less, preferably 0.5% by weight or less. When using the above-mentioned zeolite catalyst, the chlorine content in the final liquid product can be kept low as described above, especially when using a catalyst in which the metal is supported on the zeolite, the chlorine content in the liquid product can be minimized.
[0056] In addition, the proportion of olefin products in the hydrocarbon mixture obtained by the PVC waste catalytic cracking method of the present invention can be 20 mol% or more. When each component of the obtained hydrocarbon is classified into paraffins, olefins, cycloalkanes and aromatics as described above, the catalytic cracking method of the present invention can show high selectivity for olefins and relatively low selectivity for aromatics and cycloalkanes. This is inferred because in the presence of the zeolite catalyst with an average crystal size of 5-30 nm used in the present invention, the cracked products are easily diffused, resulting in less cycloalkanes and aromatic products with ring structures. In particular, the PVC waste catalytic cracking method of the present invention can show high selectivity for ethylene and propylene, and the proportion of the two components in the product can be at least 20 mol%.
[0057] Method for producing activated carbon
[0058] In addition to the above-mentioned catalytic cracking method of waste PVC, the present invention provides a method for producing activated carbon. More specifically, the activated carbon provided by the present invention can be obtained by recovering liquid products and gaseous products as useful components from the hydrocarbon mixture obtained by catalytic cracking of the above-mentioned waste PVC, and activating the remaining solid residue. The solid residue is obtained in the form of carbon.
[0059] More specifically, the present invention provides a method for producing activated carbon, which comprises the steps of: pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture (S1); and activating the solid residue in the hydrocarbon mixture (S2), wherein the zeolite catalyst has an average crystal size of 5 to 30 nm.
[0060] Step (S1) and the zeolite catalyst are the same as above, so the description thereof is omitted. Meanwhile, activation is a process of forming micropores in the solid residue, and can be performed using H2O or KOH as an activating agent. Through the activation process, a microporous structure of the activated carbon is formed, and the specific surface area and pore volume of the activated carbon are greatly increased.
[0061] More specifically, step (S2) can be carried out in an atmosphere with a moisture content of 1% by weight or less, more specifically, in an inert atmosphere. The inert atmosphere may refer to a nitrogen atmosphere or a helium atmosphere. If step (S2) is carried out in an atmosphere with a moisture content higher than the above range, the moisture in the atmosphere reacts with the carbon in preference to carbon dioxide, and inferior activated carbon may be produced when treated with steam.
[0062] The BET specific surface area of the activated carbon obtained by the activated carbon production method of the present invention can be 250 m 2 / g or more, particularly preferably 280-1200m 2 / g. In addition, the pore volume of activated carbon can be 0.50-1cm 3 / g, particularly preferably 0.50-0.70cm 3 / g. The above specific surface area and pore volume ranges of the activated carbon are significantly higher than those of the solid residue existing before activation. Therefore, when the activated carbon production method of the present invention is used, the liquid and gaseous products can be recycled as useful components, and in addition, the solid residue corresponding to the by-product can also be advantageously manufactured into activated carbon having a high specific surface area.
[0063] The activated carbon production method of the present invention may further include a washing and drying step after the above-mentioned pyrolysis step and activation step. More specifically, the activated carbon production method of the present invention includes a step (S3) of washing and drying the activated solid residue.
[0064] The solid residue through the aforementioned steps is in the form of activated carbon, and some foreign matter may be present on its surface. Therefore, the activated solid residue may be washed with water and dried to remove foreign matter from the surface. The washing in this step may be performed with distilled water, and the drying may be performed at a sufficiently low temperature such that the structure of the activated carbon does not collapse, for example, at a temperature of 40 to 60°C.
[0065] Hereinafter, the present invention will be described in more detail by examples and experimental examples to specifically illustrate the present invention, but the present invention is not limited to these examples and experimental examples. However, embodiments according to the present invention may be modified in various forms, and the scope of the present invention should not be construed as being limited to the embodiments described in detail below. Embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0066] Catalyst Preparation Example 1
[0067] Organic ammonium molecule [C6H 13 -N + (CH3)2-C6H 12 -N + (CH3)2-C6H 13 ]Br2 - Used as a zeolite structure directing agent (SDA). First, SDA organic ammonium and NaOH were dissolved in distilled water, and the solution was then stirred at room temperature for 1 hour. Thereafter, an aqueous sodium silicate solution was added thereto and stirred for another 1 hour at room temperature, and then 47 wt % sulfuric acid was added and stirred at 60° C. for 12 hours. The molar ratio of the components of the solution finally prepared by adding sulfuric acid was as follows:
[0068] 100SiO2 / 1.25Al2O3 / 30NaO / 10SDA / 24H2SO4 / 4000H2O
[0069] The prepared solution was placed in a Teflon container, and the container was placed in a stainless steel autoclave and rotated at 130° C. for 5 days. Thereafter, the formed solid precipitate was separated from the solution by filtration, dried in an oven at 100° C. for one day, and then calcined at 550° C. under flowing air to finally obtain the catalyst.
[0070] Catalyst Preparation Example 2
[0071] 1 g of the catalyst prepared in Catalyst Preparation Example 1 was added to 250 ml of 1M Ni(NO3)2 aqueous solution and stirred at room temperature for 1 hour. Then, the catalyst was separated from the solution by filtration, dried in an oven at 100°C for one day, and then calcined at 450°C under flowing air to obtain a Ni-loaded catalyst.
[0072] Catalyst Preparation Example 3
[0073] The catalyst was prepared by calcining Zeolyst's MFI zeolite (product name: CBV 5524G) at 450°C under flowing air.
[0074] Catalyst Preparation Example 4
[0075] The catalyst was prepared by calcining Tosoh zeolite (product name: HSZ-931HOA) at 450° C. under flowing air.
[0076] The BET specific surface area, pore volume, mesopore diameter and average crystal size of the catalysts prepared in Catalyst Preparation Examples 1 to 4 are summarized in Table 1 below.
[0077] [Table 1]
[0078]
[0079] Among the above-mentioned catalyst preparation examples, Catalyst Preparation Examples 3 and 4 had no mesopores due to the lack of nanocrystallinity of the catalysts, and thus the mesopore diameters could not be measured.
[0080] Example 1-1
[0081] 10 g of waste oil cloth was used as PVC waste. The waste oil cloth was washed with water and crushed, put into a pyrolysis reactor, and 1 g of the catalyst prepared in Catalyst Preparation Example 1 was also added to the pyrolysis reactor. Then, the reactor was sealed and heated to 450° C. From the moment the temperature in the reactor reached 450° C., the pyrolysis reaction was carried out for 2 hours, and as a result, a hydrocarbon mixture containing gaseous products, liquid products and solid residues was obtained.
[0082] Example 1-2
[0083] The same procedure as in Example 1-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 2 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0084] Comparative Example 1-1
[0085] The same procedure as in Example 1-1 was performed except that no catalyst was used. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product and a solid residue was obtained.
[0086] Comparative Example 1-2
[0087] The same procedure as in Example 1-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 3 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0088] Comparative Examples 1-3
[0089] The same procedure as in Example 1-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 4 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0090] Example 2-1
[0091] 10 g of waste electric wire was used as PVC waste. The waste electric wire was washed with water and crushed and put into a pyrolysis reactor, and 1 g of the catalyst prepared in Catalyst Preparation Example 1 was also added to the pyrolysis reactor. Then, the reactor was sealed and heated to 400° C. From the moment the temperature in the reactor reached 400° C., the pyrolysis reaction was carried out for 2 hours, and as a result, a hydrocarbon mixture containing gaseous products, liquid products and solid residues was obtained.
[0092] Example 2-2
[0093] The same procedure as in Example 2-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 2 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0094] Comparative Example 2-1
[0095] The same procedure as in Example 2-1 was performed except that no catalyst was used. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product and a solid residue was obtained.
[0096] Comparative Example 2-2
[0097] The same procedure as in Example 2-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 3 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0098] Comparative Example 2-3
[0099] The same procedure as in Example 2-1 was performed except that 1 g of the catalyst prepared in Catalyst Preparation Example 4 was used as the catalyst. As a result, a hydrocarbon mixture containing a gaseous product, a liquid product, and a solid residue was obtained.
[0100] The catalyst types, PVC wastes, and pyrolysis temperatures used in Examples 1-1 to 2-2 and Comparative Examples 1-1 to 2-3 are summarized in Table 2 below.
[0101] [Table 2]
[0102]
[0103] Example 3-1
[0104] Only the solid residue of the hydrocarbon mixture obtained in Example 1-1 was separated and then activated with H 2 O. The activation was performed at a temperature of 750° C. for 2 hours to finally obtain activated carbon.
[0105] Example 3-2
[0106] Activated carbon was obtained in the same manner as in Example 3-1, except that the activation temperature was 800°C.
[0107] Example 3-3
[0108] Activated carbon was obtained in the same manner as in Example 3-1, except that the activation temperature was 800° C. and the activation time was 4 hours.
[0109] Embodiment 3-4
[0110] Activated carbon was obtained in the same manner as in Example 3-1, except that KOH was used instead of H2O for activation and the activation temperature was 700°C.
[0111] Embodiment 3-5
[0112] Activated carbon was obtained in the same manner as in Example 3-1, except that KOH was used instead of H2O for activation.
[0113] Comparative Example 3
[0114] Only the solid residue of the hydrocarbon mixture obtained in Example 1-1 was separated and then subjected to heat treatment without an activation step using a separate activating agent, resulting in activated carbon.
[0115] The activation conditions in Example 3-1 and Comparative Example 3 are summarized in Table 3 below.
[0116] [Table 3]
[0117] Activator Type Activation temperature(℃) Activation time (hr) Example 3-1 <![CDATA[Activation of H2O]]> 750 2 Example 3-2 <![CDATA[Activation of H2O]]> 800 2 Example 3-3 <![CDATA[Activation of H2O]]> 800 4 Embodiment 3-4 KOH Activation 700 2 Embodiment 3-5 KOH Activation 750 2 Comparative Example 3 Not used 750 2
[0118] Experimental Example 1. Confirmation of the ratio of each product in the obtained hydrocarbon mixture
[0119] The mass ratio of the liquid product, the gaseous product and the solid residue in the hydrocarbon mixture obtained in Example 1-2 and Comparative Example 1-2 was confirmed. The ratio of each product was determined by measuring the mass of the solid residue and the liquid product after acquisition, and subtracting the mass of the solid residue and the liquid product from the weight of the reactants before the reaction, and taking the remaining weight as the weight of the gaseous product. The results are summarized in Table 4 below.
[0120] [Table 4]
[0121]
[0122] As can be seen from Table 4 above, when comparing Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-3 (in which the same PVC waste was cracked), a higher gas product ratio was confirmed in the examples, and for the solid residue, a lower solid residue ratio was confirmed in the examples. The solid residue is the least useful component among the components obtained by cracking. Therefore, it can be confirmed that when the examples of the present invention are used, more useful gas products and liquid products can be obtained with higher selectivity.
[0123] These results are also confirmed even when comparing Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3. In the case of Comparative Examples 2-1 to 2-3, a higher solid residue ratio was confirmed compared to Examples 2-1 to 2-2, and in the case of Examples 2-1 to 2-2, a higher liquid product ratio was confirmed compared to Comparative Examples 2-1 to 2-3. Which of the gaseous product and the liquid product obtained due to cracking will have a higher selectivity may vary depending on the type of PVC waste subjected to cracking. However, it can be confirmed from the above that, in general, when the cracking method of the present invention is used, the selectivity of the solid residue corresponding to the by-product can be reduced, and the selectivity for the useful component can be increased.
[0124] Experimental Example 2. Confirmation of the product ratio of each hydrocarbon type in the obtained hydrocarbon mixture
[0125] The molar ratio of paraffin, olefin, cycloalkane and aromatic product in the hydrocarbon mixture obtained in Examples 1 to 2 and Comparative Examples 1 to 2 was confirmed. The molar ratio of each product was measured using a YL Instrument 6500GC gas chromatograph (manufactured by YOUNGIN SCIENTIFIC CO., LTD.) equipped with a conductivity detector and a flame ionization detector. In the case of gaseous products, online GC analysis was used, in which the product was directly injected into the GC, and in the case of liquid products, they were separated and taken out after the reaction time and measured by GC analysis. The results are summarized in Table 5 below.
[0126] [Table 5]
[0127]
[0128] As can be seen from Table 5 above, when the cracking method according to the embodiment of the present invention is used, it is confirmed that the selectivity for olefin products is significantly higher than that of the comparative example, and the selectivity for cycloalkane products and aromatic products is generally low. Thus, it is confirmed that when the cracking method of the present invention is used, cycloalkane and aromatic products with low usefulness can be obtained with low selectivity, and olefin products with high usefulness can be obtained with high selectivity.
[0129] Experimental Example 3. Confirmation of the oil ratio of the liquid product in the obtained hydrocarbon mixture
[0130] Separate the liquid products in the hydrocarbon mixture obtained in the above-mentioned embodiment and the comparative example respectively, then check the oil ratio (based on mole) in the liquid product, and also measure the chlorine content in the liquid product. The ratio of each oil is measured by GC analysis, and the method is the same as that of Experimental Example 2, and the chlorine content is measured using an ion chromatography device equipped with a combustion module. The results are summarized in the following table 6.
[0131] [Table 6]
[0132] gasoline Kerosene + diesel wax Chlorine content (mass %) Example 1-1 88.7 10.4 0.9 0.5 Example 1-2 88.2 10.8 1.0 0.3 Example 2-1 92.6 5.6 1.8 1.1 Example 2-2 91.5 6.3 2.2 0.7 Comparative Example 1-1 71.2 27.5 1.3 4.02 Comparative Example 1-2 79.2 19.2 1.6 0.8 Comparative Examples 1-3 77.1 21.1 1.8 0.9 Comparative Example 2-1 81.0 10.7 8.3 6.1 Comparative Example 2-2 82.8 14.0 3.2 1.3 Comparative Example 2-3 80.1 15.6 4.3 1.4
[0133] As shown in Table 6 above, the liquid product obtained by the cracking method of the embodiment of the present invention has a high proportion of gasoline, and the high added value is greater than 88%, while in the case of the cracking method of the comparative example, the gasoline proportion is lower than that of the embodiment. It can be confirmed that when the cracking method of the present invention is used, the selectivity for useful components can be improved.
[0134] Furthermore, the chlorine content in the liquid product obtained when using the examples of the present invention is significantly low, and therefore, it can be seen that when using the cracking method of the present invention, the purification cost of the obtained oil can also be minimized.
[0135] Experimental Example 4. Confirmation of structural properties of the obtained activated carbon
[0136] The specific surface area and pore volume of the activated carbon obtained in Examples 3-1 to 3-5 and Comparative Example 3 were examined. The pore volume and specific surface area were measured using the ASAP 2020 device from Micromeritics. More specifically, after the activated carbon sample was pretreated at 300°C and vacuum for 3 hours, the argon isotherm adsorption curve was measured at 186°C using the above-mentioned device, and the pore size and volume were calculated by the isotherm adsorption curve. The BET specific surface area was calculated using the adsorption amount in the P / P0=0.05 to 0.2 region of the isotherm adsorption curve by the BET method, and the pore volume was calculated from the adsorption amount at P / P0=0.95. The results are summarized in Table 7 below.
[0137] [Table 7]
[0138] <![CDATA[BET specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Example 3-1 292 0.60 Example 3-2 402 0.57 Example 3-3 548 0.59 Embodiment 3-4 1000 0.54 Embodiment 3-5 1180 0.65 Comparative Example 3 40 0.05
[0139] As shown in Table 7 above, it was confirmed that when activated carbon was obtained by activating the solid residue obtained by the cracking method of the present invention, the activated carbon could have a high specific surface area and a high pore volume.
Claims
1. A method for catalytic cracking of PVC waste, comprising the step of pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture (S1), The zeolite catalyst has an average crystal size of 5 nm to 30 nm.
2. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the zeolite catalyst is loaded with at least one metal selected from the group consisting of Ni, Cu, Fe and Mn.
3. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the zeolite catalyst has mesopores with a diameter of 5 nm to 30 nm.
4. The method for catalytic cracking of PVC waste according to claim 1, wherein the BET specific surface area of the zeolite catalyst is 300 m 2 / g to 400m 2 / g.
5. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the pore volume of the zeolite catalyst is 0.25 cm 3 / g to 0.35cm 3 / g.
6. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the pyrolysis is carried out at 400°C to 500°C.
7. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the pyrolysis is carried out for 1 hour to 6 hours.
8. The method for catalytic cracking of PVC waste according to claim 1, wherein the PVC content of the PVC waste is greater than 20% by weight.
9. The method for catalytic cracking of PVC waste according to claim 1, wherein the proportion of olefin products in the hydrocarbon mixture obtained in step (S1) is greater than 20 mol%.
10. The method for catalytic cracking of PVC waste as claimed in claim 1, wherein the hydrocarbon mixture obtained in step (S1) comprises a gaseous product, a liquid product and a solid residue.
11. The method for catalytic cracking of PVC waste according to claim 10, wherein the Cl content in the liquid product is 1 wt% or less.
12. A method for producing activated carbon, the method comprising the following steps: Pyrolyzing PVC waste in the presence of a zeolite catalyst to obtain a hydrocarbon mixture (S1); and activating the solid residue (S2) in the hydrocarbon mixture, The zeolite catalyst has an average crystal size of 5 nm to 30 nm.
13. The method for producing activated carbon according to claim 12, wherein H 2 O or KOH for activation.
14. The method for producing activated carbon according to claim 12, wherein the activated carbon has a BET specific surface area of 250 m 2 / g or above.
15. The method for producing activated carbon according to claim 12, wherein the pore volume of the activated carbon is 0.50 cm 3 / g to 1cm 3 / g.
Citation Information
Patent Citations
A catalytic process of simultaneous pyrolysis of mixed plastics and dechlorination of the pyrolysis oil
CN109563413A
Zeolites, the production thereof, and their uses for upgrading heavy oils
CN110621401A
New zeolite catalyst and production thereof
JP1995308581A
Method of manufacturing activated carbon
JP2008056512A
Artificial neural network-based custom rice cake subscription service providing system and method therefor
KR102392173B1